Enhanced ferroelectric properties of La-substituted BiFeO3 thin films on LaSrCoO3/Pt/TiO2/SiO2/Si (100) substrates prepared by the soft chemical method - Simões, Alexandre Zirpoli [UNESP]; Ramirez, M. A. [UNESP]; Foschini, C. R. [UNESP]; Moura, F.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2012)
Bi0.85La0.15FeO3 (BLFO015) thin films were deposited by the polymeric precursor solution on La0.5Sr0.5CoO3 substrates. For comparison, the films were also deposited on Pt bottom electrode. X-ray diffraction data confirmed the substitutions of La into the Bi site with the elimination of all secondary phases under a substitution ratio x = 15% at a temperature of 500 degrees C for 2 h. A substantial increase in the remnant polarization (P-r) with La0.5Sr0.5CoO3 bottom electrode (P-r approximate to 34 mu C/cm(2)) after a drive voltage of 9 V was observed when compared with the same film deposited on Pt substrate. The leakage current behavior at room temperature decreased from 10(-8) (Pt) to 10(-10) A/cm(2) on (La0.5Sr0.5CoO3) electrode under a voltage of 5 V. The fatigue resistance of the Au/BLFO015/LSCO/Pt/TiO2/SiO2/Si (1 0 0) capacitors with a thickness of 280 nm exhibited no degradation after 1 x 10(8) switching cycles at a frequency of 1 MHz. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Films; Interfaces; Dielectric properties; Ferroelectric properties